2016
DOI: 10.1111/jpc.13009
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea in children with obesity

Abstract: Ethnicity was a significant factor with more obese ATSI children having OSA. The significant correlation between hs-CRP with OEI is consistent with findings of previous studies. Several factors (glycosylated haemoglobin, LDL) approached significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…[2][3][4] Children with underlying medical conditions, including obesity, craniofacial anomalies, neuromuscular disorders, and certain genetic syndromes, have higher rates of OSA. [5][6][7][8] Clinical history is poorly predictive of the diagnosis, and polysomnography is required for the diagnosis of OSA. 5,6 Pulmonary hypertension (PH), an abnormal elevation in pulmonary artery pressure, is commonly reported as a cardiovascular sequelae of OSA.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Children with underlying medical conditions, including obesity, craniofacial anomalies, neuromuscular disorders, and certain genetic syndromes, have higher rates of OSA. [5][6][7][8] Clinical history is poorly predictive of the diagnosis, and polysomnography is required for the diagnosis of OSA. 5,6 Pulmonary hypertension (PH), an abnormal elevation in pulmonary artery pressure, is commonly reported as a cardiovascular sequelae of OSA.…”
Section: Introductionmentioning
confidence: 99%
“…37 Obese ATSI children have also been found to be at a greater risk of having OSA than non-ATSI obese children. 38 However, a study on primary school children in the Northern Territory did not find a significant association between race and SRBD, with similar rates of sleep breathing problems identified in both ATSI (3%) and non-ATSI (2%) groups. 39 As a possible implication of the present findings, it has been suggested that there is a significant association between OSA and poor school performance, 40 and OSA management is associated with improved school performance.…”
Section: Discussionmentioning
confidence: 92%
“…4 and 5, Table 3). Obstructive sleep apnea is a subtype of sleep apnea syndrom that is principally associated with a narrowed upper airway that has resulted from fat accumulation accompanied with obesity or other congenital or acquired conditions (Dudley and Patel 2016;Kassim et al 2016). Because For each participant, the amount of salivation was measured for 1 min during resting and various tasting states using the indicated tastants.…”
Section: Discussionmentioning
confidence: 99%
“…This is known as oral appliance therapy (Clark et al 2000;Hosoya et al 2014;Bender 2016;Lavigne and Sessle 2016). At present, obstructive sleep apnea is principally believed to be associated with a narrowed upper airway (Dudley and Patel 2016;Kassim et al 2016). Thus, clarifying the abovementioned associations would be important to the field of sleep medicine, especially in countries with relatively short sleeping times, such as Japan.…”
Section: Introductionmentioning
confidence: 99%